Perforator flaps for reconstruction of lower limb defects - Yasir, Mir; Wani, Adil Hafeez; Zargar, Haroon Rashid (International Surgery Journal, 2016)
Background: Reconstruction of soft tissue defects in the lower third of the leg remains challenging. Anatomical constraints limit the local options available for complex defects especially lower third of leg. Local flaps based on perforator vessels are raising interest in reconstructive surgery of the limbs. We present our experience with perforator flaps for reconstruction of soft tissue defects in the lower limb. Methods: The study was carried prospectively and 23 patients with lower limb defects treated with various perforator flaps (both elective as well as emergency) were included in the study. A hand-held Ultrasound Doppler was used preoperatively and intraoperatively to detect the perforator vessels. Results: Out of 23 patients, we witnessed partial flap loss in 1 and distal flap necrosis in 3 patients. 4 patients had minor complications which included infection, wound dehiscence and congestion of flap. Conclusions: Perforator flaps may represent a good alternative to the free flaps in the areas were other local reconstructive procedures are not possible. This is a versatile technique and with decreased donor site morbidity limited to a single body area. There is a specific like to like soft tissue replacement leading to a better cosmetic and reconstructive outcome. The main drawback of the perforator flaps however is the higher risk of venous congestion.